PROSPECÇÃO DE MICRORGANISMOS COM POTENCIAL PROBIÓTICO CONTRA ENTEROPATÓGENOS BACTERIANOS. - CARMO, Monique Santos do (2019)
Bacterial diarrhea is an infectious disease that occurs with significant morbidity and mortality worldwide, principally in underdeveloped and developing countries. The recommended protocols for treatment include hydro-electrolyte replacement, eventually associated with antimicrobials. However, such measures are not sufficient to eliminate all deleterious effects of this infectious process, such as reduction in the number of evacuations and restoration of the intestinal microbiota. More rational measures could include approaches that can aid in the prevention and/or treatment of intestinal infection, without increasing the imbalance of the microbiota and without exerting selective pressures that could lead to the emergence of resistant microorganisms. One possibility consists in the use of probiotics, however, different studies have shown that many beneficial effects of these microorganisms can be species-specific or even strain-specific. Thus, not all probiotics may be active against enteropathogenic bacteria commonly associated with diarrheal disease. Therefore, the objective of this study was to prospect for microorganisms in newborns’ feces with probiotic potential against prevalent bacterial enteropathogens. Stool microbiological cultures were performed in selective culture media for Bifidobacterium and Lactobacillus. Typical gram-positive and catalase-negative bacilli colonies were submitted to bile salt tolerance, acid pH and lysozyme tests and binding ability to mucin. The bacterial isolates with probiotic profile were analyzed for antimicrobial activity against enteropathogenic bacteria and also for the inhibitory activity of adhesion to mucin. Subsequently, the bacteria were identified by sequencing the 16S rRNA. It was produced a review article on the main probiotic mechanisms of action and clinical perspectives for treatment and prevention of diarrhea in children. Additionally, an article resulting from the investigation of the probiotic potential of the isolates of Bidifidobacterium bifidum 14.2, Bidifidobacterium longum subsp. longum 25.3, B. longum 49.3, Bidifidobacterium animalis subsp. lactis 56.1 and Lactobacillus fermentum 54.2, as they were resistant to acid pH, bile salts, lysozyme and showed mucin binding was written. Additionally, these strains inhibited binding to mucin and the growth of enteropathogens, such as: enteroaggregative Escherichia coli 042 (EAEC 042), enteropathogenic E. coli e2348/69 (EPEC e2348/69), enterohemorrhagic E. coli 933 EDL (EHEC 933 EDL), enterotoxigenic E. coli 1661-1 (ETEC 1661-1), Salmonella Choleraesuis INCQS 028, and Shigella flexneri 2a. The data obtained are promising and provide supports for the future use of these potential probiotics in animal tests to confirm their efficacy in experimental infection models.